A strategy to increase identification of patients with Familial Hypercholesterolemia: Application of the Simon Broome lipid criteria in a large-scale retrospective analysis - James K. Fleming; Renee M. Sullivan; David Alfego; Natalia T. Leach; Tamara J. Richman; Jill Rafalko (American Journal of Preventive Cardiology)
Introduction: Familial Hypercholesterolemia (FH) is a primarily autosomal dominant condition characterized by markedly elevated low-density lipoprotein-cholesterol (LDL-c) and an increased risk of atherosclerosis and cardiovascular disease (CVD). Though early identification and treatment are crucial to optimizing outcomes, few laboratory strategies exist to detect FH. Methods: All lipid tests for total cholesterol (TC) and LDL-c ordered through a large nation-wide network of medical laboratories in the United States (US) from 2018 - 2022 were retrospectively evaluated using a decision tree algorithm based on Simon Broome lipid criteria. If thresholds were met, results were classified as “possible FH” or as “no lipid evidence of FH” if not met. Results: The review of 121,141,307 lipid panels and associated genetic tests from 58,400,105 patients resulted in 1,843,966 (3.2 %) that were classified as “possible FH”. Overall, the mean TC was higher in females than males, particularly in those ≥16 years. LDL-c in the “no lipid evidence of FH” cohort increased year-over-year; LDL-c was stable or decreased in the “possible FH” cohort. Despite the large number of patients classified with “possible FH”, very few (0.02 %) matched patients had genetic testing. Conclusion: A laboratory-developed algorithm using Simon Broome lipid criteria can help identify patients who may benefit from additional FH evaluation. While critical, testing hyperlipidemic children for FH is grossly underutilized, as is genetic testing for FH. Diagnostic laboratories are uniquely positioned to bring FH to the attention of clinicians, with the goal of earlier diagnosis, cascade testing, and appropriate treatment.